Litigation Analisis Studi Kasus Sengketa Tanah dan Penyelesaiannya melalui Hukum Acara Perdata: Pendekatan Litigasi dan Non-Litigasi: Analisis Penyelesaian Melalui Litigasi dan Non-Litigasi dalam Hukum Acara Perdata - Rina Mugi Lestari; Renata Safa Putri; Ghevy Adyariza; Praja Syukur Harahap; Vinni Aryanti; Muhammad Zhabi Montela; Siswajanthy, Farahdinny (Jurnal Sains Indonesia, 2025)
Land disputes are one of the most common types of conflict in Indonesia and have significant social, economic and legal impacts. Land dispute resolution can be pursued through two main approaches, namely litigation (court channels) and non-litigation (alternative out-of-court settlements). This research aims to analyze the land dispute settlement process based on a concrete case study using a civil procedural law approach. The method used is descriptive qualitative, with data collection through the study of relevant legal literature. The results show that the settlement of land disputes through litigation provides legal certainty through court decisions, but often requires considerable time and costs. In contrast, non-litigation settlements such as mediation and negotiation offer faster and more efficient solutions, but require good faith and agreement of the parties. This study emphasizes the importance of an in-depth understanding of civil procedural law in managing land disputes and the need for integration between litigation and non-litigation mechanisms to achieve fair and sustainable settlements.